IbM WIRA USAHA PANTI ASUHAN MELALUI RANCANG BANGUN ALAT PEMBUAT ROTI DI KECAMATAN RUNGKUT DAN KEBONSARI SURABAYA - Endang Setyowati; Sajiyo Sajiyo; Ida Ayu Sri Brahmayanti; Ida Ayu Nuh Kartini (JPM17: Jurnal Pengabdian Masyarakat, 2015)
Reformatory as social worker represent a[n service place which can assistskilled [of] child take care of, especially Orphan reformatory " Siti Fatimah"and reformatory Putri " Aisyiyah II" Surabaya. Pursuant to result of surveyantecedent and result of interview of problems [of] arising out [is] the lack ofeducation and skill, especially skill instructing [at] enterprenuership. From theproblems above hence solution which on the market to face the problems ofReformatory of Orphan of Siti Fatimah and the following ReformatoryKebonsari : a) give the skill in making bread; b) make the appliance of ovenbread and its equipment; and adjacent c)memberikan by kontinue (berkesinambungan)so that the orphan can make the bread and become theenterprenuership Result from activity program this Ibm, in the form of preciseadjusment of technology utilize the oven of bread and method of bread making,with the expectation capacities 3200 pcs / day ( 400 pcs / clock ). Sedanhgkandesign to develop;build the oven bread with the specification and size measureof oven of bread sbb : substance oven from stainles steel, long : 40 Cm ; wide :30 Cm; high : 30 Cm ; Jjmlah Rack : 3 Rack; capacities : 200 pcs / clock ; andsum up the Unit : 2 Excellence design to develop;build the oven bread : Formthe simple oven, part of back part step aside for convex impress the ergonomisand more guaranting [of] security to hand or organ yan come into contact with.40 x 30 Cm highly 30 Cm, lighter disampning also only need the small